Aqueous Flare as an Indicator of Response to Dexamethasone Treatment in Retinal Vein Occlusions: A Pilot Study. (3rd May 2016) - Demirel, Sibel; Yanık, Özge; Batıoğlu, Figen; Özmert, Emin; Baş, Zeynep
Abstract: Purpose : To investigate aqueous flare change patterns in retinal vein occlusions (RVO) following intravitreal application of dexamethasone implant. To evaluate the correlations between central macular thickness (CMT), best corrected visual acuity (BCVA) and aqueous flare values. Methods : This prospective, interventional pilot study included 40 eyes of 40 patients with macular edema associated with RVO. All patients received intravitreal injection of dexamethasone implant at baseline visit. Full ophthalmologic examination, CMT and aqueous flare measurements were performed prior to injection and repeated at months 1, 3, and 5. Aqueous flare, BCVA and CMT changes between visits were assessed. Further statistical analysis was performed to investigate correlations between these three parameters. Results : The patients consist of 23 (57.5%) men and 17 (42.5%) women with a mean age of 65.7 ± 6.2 years. Of the 40 eyes, 24 (60%) had branch retinal vein occlusion and 16 (40%) had central retinal vein occlusion. BCVA (log MAR) was significantly correlated with aqueous flare at each visit ( r  = 0.436, p   = 0.005; r  = 0.349, p  = 0.027; r  = 0.357, p  = 0.024; r  = 0.551, p  = 0.000, respectively). Flare values were also correlated with CMT measurements in 3rd and 5th months ( r  = 0.324, p  = 0.042; r  = 0.556, p  = 0.000, respectively). Comparing the percentage change in CMT and flare values over time, the change in CMT from baseline to 3rd and 5th months ( r  = 0.441, p  = 0.004, r  = 0.448, p  = 0.004), from 1st month to 3rd and 5th months ( r  = 0.441, p  = 0.004; r  = 0.461, p  = 0.003) and from 3rd month to 5th month were directly correlated with aqueous flare changes ( r  = 0.584, p  = 0.000). Twenty-two eyes (55%) required second dexamethasone implant application at 5th month. Conclusion : Considering the inflammatory base of RVO, dexamethasone implants effectively decreased the flare values in the anterior chamber. The CMT change was directly correlated with aqueous flare values.